The Effect of Self– Care Teaching by Video Tape on Physical Problems and Quality of Life in Dialysis Patients - Shahram Baraz-Pardenjani; Esa Mohammadi; Behrouz Boroumand (نشریه پرستاری ایران, 2008)
Background and Aim: In patients with a chronic disease such as end-stage renal disease (ESRD), for which cure is not a realistic goal, maximizing patients’ function and well-being should be a primary objective of care. However, quality of life in dialysis patients is lower than normal. This study is aiming to examine the effect of self–care educational package programs on physical problems and quality of life in dialysis patients.   Material and Method: The study was conducted by quasi-experimental pretest-posttest design in educational hospitals of Iran and Tehran medical science universities in 2004-2005. Thirty one patients were selected on the basis of a non-randomized sampling. Each patient was assessed before starting the dialysis treatment by questionnaires about educational requirements, quality of life (SF-36) and checklist. Laboratory variables were recorded as the average for last two months prior to the education. After implementing an educational program on the basis of existing problems it was recorded. This movie was shown to the patients during one month once a week while they were on the dialysis. At the end of educational period, laboratory variables (average for last two months) were recorded and quality of life questionnaire and checklist were completed. Data were analyzed with descriptive statistics, Paired T Test, Independent T, Macknemar and wilcoxon tests.   Results: Findings showed that there was a significant decreases in serum urea (P=0.020), serum uric acid (P= 0.002), serum phosphate (P= 0.002), interdialytic weight gain (P= 0.000), systolic blood pressure (P= 0.045), diastolic blood pressure (P= 0.004), edema (P= 0.000), skin itching (P=0.000), local vascular problems (P= 0.031) and increase in Ca (P= 0.000) and improvement in quality of life score (P= 0.002).   Conclusion: Providing dialysis patients with self– care educational package programs had a positive influence on decreasing the problems and improving the quality of life.